IMPLEMENTASI KONSEP PENDIDIKAN SIT (SEKOLAH ISLAM TERPADU) DI SMPIT ISHLAHUL UMMAH LEUWILIANG BOGOR - Angelria Septiani; Musthafa Zahir; Nailil Muna Shalihah; Ahmad Farid (JURNAL ILMIAH RESEARCH STUDENT, 2024)
Integrated Islamic school education is a model of educational institution that seeks to combine general knowledge and religion in one integrative curriculum package that implements the concept of Islamic education based on the Qur'an and As-Sunnah. The operational concept of SIT is an accumulation of the processes of acculturation, inheritance and Islamic civilization from generation to generation. The focus of this research is: the implementation of the concept of integrated Islamic education in the form of its application in the curriculum and activities at the SIT educational institution at SMPIT Ishlahul Ummah. This research uses a descriptive method with a qualitative approach. The research data collection method uses observation, interviews and documentation.The research results show that: (1) The concept of integrated Islamic education is the process of implementing education by combining scientific education and religious education into one curriculum. With this approach, all school subjects and activities are guided by the teachings and messages of Islamic values. SMPIT Ishlahul Ummah, which in its learning process refers to integrated Islamic education, namely integrated learning using the national education curriculum and also using a typical curriculum.